Using longitudinal data to understand the effects of HIV and AIDS on livelihoods - Samuels, Fiona; Drinkwater, Michael; McEwan, Margaret (International Food Policy Research Institute, 2006)
There are few longitudinal studies looking at the effects of HIV and AIDS over time on individuals, households and communities. One exception to this is a study conducted in two locations in Zambia: the first study was carried out in 1993, the second in 2005. The 1993 study looked at the impacts of HIV and AIDS on livelihoods; the re-study aimed to understand what had happened in the intervening period—both in terms of impacts, as well as the adaptability and resilience of households and communities to HIV and AIDS. The study was also unique in its methodology, using the concept of ‘cluster’ as a unit through which to understand how individuals and households adapted or disintegrated as a result of ill health, and specifically AIDS.